Safety and effectiveness of His-bundle pacing and left bundle branch pacing (conduction system pacing) as a first option for cardiac pacing – results of a single-center. (3rd October 2022) - Slater, C; Camanho, L E M; Saad, E B; Inacio Jr, L A O; Dias, L C; Santos, G V; Mourilhe-Rocha, R
Abstract: Background: Conduction system pacing (CSP) (His bundle pacing and left bundle pacing) is a group of techniques intended to achieve cardiac pacing with a narrow QRS complex through a lead directly inserted in conduction system structures. The safety and effectiveness of this technique are not yet fully understood. Purpose: To describe the short-term implant findings and safety profile of CSP as a first option after 4 years in a single center. Methods: In a period of 42 months, 214 patients were submitted to CSP as a first strategy to restore AV synchrony (pacemakers for AV block or sinus node dysfunction) or as a resynchronization (CRT) strategy (for patients with heart failure and bundle branch block). CSP lead was implanted in lieu of a conventional right ventricular lead in pacemaker cases, and in addition or in lieu of a coronary sinus lead, in CRT cases, depending on the technical and anatomical possibilities. Results: The mean age was 76.7±16.4 years, 65% males. 162 patients implanted a CSP lead for a dual-chamber pacemaker, 3 patients for a single chamber pacemaker, 32 patients for CRT-D (CSP lead replacing the coronary sinus lead with a defibrillator), and 13 patients for an optimized CRT (CSP lead plus coronary sinus lead). In 16 patients (7.4%) the technique of choice was His bundle pacing, two of them presented with subacute elevated thresholds, requiring new lead implantation at the moment of generator pulse replacement. One patient submitted to left bundle branch pacing (0.4%) had subacute lead dislodgement, being submitted to lead revision. Four patients intended for CRT (1.8%) didn't meet the criteria for His bundle pacing or left bundle branch pacing, being submitted to conventional coronary sinus lead placement. There were 10 cases (4.6%) of confirmed lead perforation during the lead septum insertion, with prompt repositioning, all uneventful. No pericardium effusion related to lead perforation was observed. One patient (0.4%) had a pneumothorax, requiring chest tube drainage. Conclusion: Conduction system pacing as a first strategy is a feasible, effective and safe technique, both for pacing and for resynchronization purposes, with a complication rate comparable to conventional implantation. Funding Acknowledgement: Type of funding sources: None.